ANGLE GRINDER STAND AS A SUPPORTIVE TOOL FOR CUTTING METAL PROCESS - Jirin, Mohd Sazali; Edwin, Silver; Kining, Pounsin; Majimin, Peter; Saili, Amza; Idek, Sirhajwan (MATTER: International Journal of Science and Technology, 2020)
The goal of this project was to examine the plausibility of a supplementary tool known as “Angle Grinder Stand” that can possibly aid the process of metal cutting in producing metal plates that were cut properly according to required measurements. There were 30 students from a welding technology programme of a local vocational institution who tested this tool and were required to express their ratings on its function and features by completing questionnaires. The findings revealed that the students found this tool efficient, safe, useful and easy to use. This suggested that this tool could be potentially replicated and promoted across vocational institutions and factories in order to provide welders an improved experience in cutting metal plates and other types of materials of a better quality.